Discussions about economic growth in roman world: an analytical approach through the use of Household Archaeology - Mañas Romero, Irene; Bermejo Tirado, Jesús (Gerión. Revista de Historia Antigua, 2013)
This paper analyses the introduction of the growth concept in Ancient History, and tries to understand the reasons of this introduction, as well as the impact that this notion has had in this area and the methodological lacks related to it. Finally, we propose the application of the Household Archaeology as a possible framework for the Ancient Economy studies.
Keywords: Economic History; Growth; Archaeology; Domestic units.